2009
DOI: 10.1084/jem.20091430
|View full text |Cite
|
Sign up to set email alerts
|

Thymic development beyond β-selection requires phosphatidylinositol 3-kinase activation by CXCR4

Abstract: T cell development requires phosphatidylinositol 3-kinase (PI3K) signaling with contributions from both the class IA, p110δ, and class IB, p110γ catalytic subunits. However, the receptors on immature T cells by which each of these PI3Ks are activated have not been identified, nor has the mechanism behind their functional redundancy in the thymus. Here, we show that PI3K signaling from the preTCR requires p110δ, but not p110γ. Mice deficient for the class IB regulatory subunit p101 demonstrated the requirement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
168
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(183 citation statements)
references
References 54 publications
13
168
0
Order By: Relevance
“…Homing properties and the numbers of early thymic progenitors were not determined but would be of interest in the future. However, our observation of a reduction of DN4 T cells upon Nes cell-specific deletion of Rarg fits with the importance of CXCL12 in DN3-to-DN4 transition (49,50). Because of significant germline deletion issues, we have not been able to obtain sufficient mice to determine whether loss of Rarg in Nesexpressing CDR1 + EpCAM 2 thymic stromal cells results in deregulated expression of Cxcl12 or Scf, but these studies would also be of interest.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Homing properties and the numbers of early thymic progenitors were not determined but would be of interest in the future. However, our observation of a reduction of DN4 T cells upon Nes cell-specific deletion of Rarg fits with the importance of CXCL12 in DN3-to-DN4 transition (49,50). Because of significant germline deletion issues, we have not been able to obtain sufficient mice to determine whether loss of Rarg in Nesexpressing CDR1 + EpCAM 2 thymic stromal cells results in deregulated expression of Cxcl12 or Scf, but these studies would also be of interest.…”
Section: Discussionsupporting
confidence: 64%
“…5B). The reduction of DN1 and DN4 cells in the Nes:Rarg D/D R26eYFP mice was indicative of a CXCL12 defect, because CXCL12 is required for homing of immature T cell progenitors to the thymus (48), in addition to b selection and differentiation beyond the DN3 stage (49,50). To determine whether the CDR1 + stroma expressed Cxcl12, we separated CDR1 + stromal cells based on eYFP expression and performed gene expression analysis of Cxcl12 and other T cell growth factors.…”
Section: ) Cdr1mentioning
confidence: 99%
“…Recovery of CD27 low cells was considerably reduced, again confirming that survival (Fig. 3) and consequent differentiation of DN3 cells are dependent upon a productive TCR-b rearrangement.While in vivo, CXCR4 was shown to be required for the progression of thymocyte differentiation beyond the DN1 stage [49], a recent report suggested that it also contributed to the b-selection-dependent transition from DN3 to DP [41,42]. We could show that the dependence on the CXCR4 ligand CXCL12 (also known as SDF-1a) was not absolute, but its addition did result in a four-fold increase in cell recovery.…”
mentioning
confidence: 69%
“…It was recently suggested that PI3 kinase signaling mediated by CXCR4 is also involved in the DN3 to DP transition [40][41][42]. To evaluate the contribution of CXCL12 during this differentiation step in the present culture system, we sorted DN3 cells and cultured them in the presence of 10 nM CXCL12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation